Transatlantic arias : early opera in Spain and the new world - Gasta, Chad M. (Chad Michael) (Biblioteca Aurea hispánica ;, 2013)
Employing current theories of ideology, propaganda and musical reception, [this book] examiness the development and impact of early opera in Spain and the Americas through close examination of the New World's first three extant operas. What emerges is an amazing history of extraordinarily complex lyrical and musical works for their time and place, which are also critical for illuminating inimitable perspectives on the cohabitation and collaboration of indigenous groups and Europeans. -- Book cover.